Ritual Tolak Bala Suku N’tuka - Fransiska Mery Angelina; Maria Fransiska (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
This research aims to determine the sequence and rhyme of the N’tuka’ tribe's mantra to repel reinforcements in Nanga Mahap. This mantra is one of several mantras in the N’tuka’ tribe. The method used in collecting data for this study is the observation method. The data obtained is then analyzed using qualitative methods, the data is analyzed as is without reducing or adding to the facts found. The results of this research are that in a series of traditional rituals for rejecting reinforcements there are symbols, including equipment such as: male pig, dog, chicken, pulut flour, jeribang banana, yotak longa, and yellow rice. The rhymes in the N’tuka’ tribe's repellent ritual mantra consist of open rhyme, closed rhyme and initial rhyme, while the rhythm not only contains magic and sacredness, but also contains aesthetic.